IDEATIONAL FUNCTION IN THE SHORT STORY FRIENDS BY MICHIWICHI - Agneso Feronika Limbong; Diane Sarima Lestari Simbolon; Lendawati Manurung; Sarah Nasrani Gea; Rina Octavia Simarmata (Merwinspy Publisher, 2025)
This study investigates the ideational metafunction within the framework of Systemic Functional Linguistics (SFL), with a specific focus on Michiwichi's short story Friends. This research aims to find out the types of processes that exist in the story. Four types of processes occur, namely material process, mental process, relational process, and verbal process. Language is examined not merely as a means of communication but also as a vehicle for constructing and representing experiential meaning. The analysis employs the transitivity system, which includes material, mental, relational, and verbal processes to explore how experiences are linguistically structured in the narrative. Adopting a descriptive qualitative approach, the research classifies each clause according to its transitivity elements (process, participant, and circumstance). The findings reveal that the text utilizes diverse process types to encode meaning, with material processes being the most prevalent, followed by mental and relational processes. These results demonstrate how linguistic features are deliberately employed to express the characters' emotions, motivations, and social dynamics. The study underscores the relevance of SFL in literary analysis and affirms that even brief fictional works can provide valuable insights for functional linguistic examination.